The Feasibility of Reactive Dye in PVA Films as High Dosimeter - Shaheen Akhtar,; Taqmeem Hussain,; Aamir Shahzad,; Qamar-ul-Islam, (Journal of Basic & Applied Sciences, 2021)
The gamma dosimetric response of the Methylene Blue (MB) in Polyvinyl Alcohol (PVA) films was investigated. The spectrophotometric analysis was done to observe the changes in these films at pre and post irradiation. The PVA based films were irradiated using Cs137 γ-source within dose range (100-200) kGy. The effect of concentration of dyes, pH of the dyed solutions and thickness of dyed films were employed as the dosimetric parameters in this study. The stability of MB-PVA films before and after irradiation was examined at ambient temperature. MB-PVA films were found to be light sensitive. Owing to simple preparation and absence of any toxic solvents during preparation, PVA based films were found to be docile for large-scale production and application for routine irradiation processes of medical equipments.